Epidemiological Characteristics and Mortality of Primary Lung Cancer Patients Admitted to the Intensive Care Unit and Undergoing Invasive Mechanical Ventilation - Hamide Gül Özdemir; Melda Türkoğlu; Şahender Gülbin Aygencel; Nazlıhan Boyacı; Kamil İnci; Sinan Özdemir (Academic Journal of Health, 2026)
Background and Aim: Lung cancer is a leading cause of cancer-related mortality globally. Patients frequently require intensive care unit (ICU) admission and invasive mechanical ventilation (IMV) due to disease progression, organ failure, or complications. This study aimed to characterize the demographic and clinical features, survival outcomes, and prognostic factors in patients with primary lung cancer receiving IMV. Materials and Methods: This retrospective, descriptive, cross-sectional study evaluated 84 primary lung cancer patients who were admitted to the Internal Medicine ICU of Gazi University Faculty of Medicine Hospital and received IMV between 2019 and 2024. Data regarding demographics, clinical scoring systems (APACHE II, GCS, SOFA), IMV indications, complications, and laboratory values on the day of IMV initiation were analyzed. Results: The study cohort demonstrated an exceptionally high mortality rate of 95.2%, with 80 non-survivors and 4 survivors. Clinical scoring systems (GCS, SOFA, APACHE II), as well as the timing and indications for IMV, were not significantly associated with mortality. However, sepsis/septic shock developed in 87% of patients during their ICU stay and was significantly associated with higher mortality (p=0.006). Furthermore, laboratory parameters evaluated on the day of IMV initiation revealed that higher lactate (p=0.042) and C-reactive protein (CRP) levels (p=0.024), alongside lower albumin levels (p=0.015), were statistically significantly associated with increased mortality. Conclusion: The mortality rate among primary lung cancer patients requiring IMV is markedly high. Mortality is significantly associated with critical illness-related factors, specifically the development of sepsis or septic shock, hypoalbuminemia, and elevated CRP and lactate levels. These findings highlight the importance of assessing the patient's acute systemic inflammatory and metabolic responses alongside the underlying malignancy.